Testing software and systems 23rd IFIP WG 6.1 International Conference, ICTSS 2011, Paris, France, November 7-10, 2011. Proceedings - Wolff, Burkhart 1962-; Zaïdi, Fatih (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the 23rd IFIP WG 6.1 International Conference on Testing Software and Systems, ICTSS 2011, held in Paris, France, in November 2011. The 13 revised full papers presented together with 2 invited talks were carefully selected from 40 submissions. The papers address the conceptual, theoretic, and practical problems of testing sofware systems, including communication protocols, services, distributed platforms, middleware, controllers, and security infrastructures.